Efektivitas Bimbingan Kelompok dengan Teknik Modeling untuk Meningkatkan Self-Awareness Mahasiswa - Indah Maya Sari; Zhila Jannati; Lena Marianti (Scidacplus, 2024)
Self awareness is a person's ability to understand feelings, actions, reasons, motivations and thoughts regarding how they should behave towards themselves and their environment. However, the phenomenon that occurs in students of the Islamic Counseling Guidance Study Program at UIN Raden Fatah Palembang turns out that not all students have high self awareness. Therefore, need to be made to help these students increase their self awareness, namely through group guidance services using modeling techniques. So, this research is entitled